PENGARUH SPIRITUALITAS DAN KECERDASAN EMOSIONAL TERHADAP KESEJAHTERAAN KARYAWAN DENGAN PERILAKU MENYIMPANG DITEMPAT KERJA SEBAGAI PEMODERASI - Elsada, Christine (AKSIOMA : Jurnal Manajemen, 2022)
This study aims to determine the effect of spirituality and emotional intelligence on the employees well-being with deviant behavior in the workplace as a moderator. The population in this study were nurses at Siloam Kupang Hospital, Siloam Labuan Bajo Hospital, and Siloam Bali Hospital who served in the inpatient room. The research sample was 154 respondents with a questionnaire as a data collection tool. The model in this study was analyzed using PLS (Partial Least Square). The results showed that spirituality and emotional intelligence had a positive and significant effect on employee well-being, organizational deviant behavior had no effect on employee well-being, interpersonal deviant behavior had a negative and significant impact on employee well-being, organizational deviant behavior moderated the relationship between spirituality and emotional intelligence on employee well-being, and Interpersonal deviant behavior does not moderate the relationship between spirituality and emotional intelligence on employee well-being